GERAKAN SADAR STUNTING (GSS): EDUKASI PUBLIK DALAM UPAYA PENCEGAHAN STUNTING GUNA MENDUKUNG PROGRAM PEMERINTAH KABUPATEN KUBU RAYA - Azrita Mardhalena; Anny Riwayati; Mutmainnah Mutmainnah; Dwi Nur Handayani (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Cases of stunting in Indonesia must be addressed immediately because the long-term impact of stunting can affect the quality of human resources in the future. One of the factors that will make a country successful can be seen in the quality of its human resources. According to the Ministry of Health, the results of the Indonesian Nutrition Status Survey (SSGI) state that the prevalence of stunting in Indonesia has decreased from 24.4% in 2021 to 21.6% in 2022. This shows that a decrease of 2.8% is still far from expectations and will drop by 14% in 2024. To prevent stunting, one must have the community's ability to know what can cause stunting in their children. So that with the community's ability to restrain, it is hoped that it can prevent stunting in children. This PKM activity provides counselling about stunting in Lingga Village, Sungai Ambawang District, Kubu Raya Regency, West Kalimantan, hoping the community will understand more about restraining to prevent it rather than treat it. The PKM FISIP UNTAN team collaborated with a resource person from ITEKES Muhammadiyah so that the community could immediately get stunting material from the experts. It is hoped that the PKM participants who attend can work together to prevent stunting in children in their area.